1998
DOI: 10.1128/mcb.18.8.4605
|View full text |Cite
|
Sign up to set email alerts
|

3′-Processed mRNA Is Preferentially Translated in Chlamydomonas reinhardtii Chloroplasts

Abstract: 3-end processing of nucleus-encoded mRNAs includes the addition of a poly(A) tail that is important for translation initiation. Since the vast majority of chloroplast mRNAs acquire their 3 termini by processing yet are not polyadenylated, we asked whether 3 end maturation plays a role in chloroplast translation. A general characteristic of the 3 untranslated regions of chloroplast mRNAs is an inverted repeat (IR) sequence that can fold into a stem-loop structure. These stem-loops and their flanking sequences s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 56 publications
(89 reference statements)
0
35
0
Order By: Relevance
“…On the other hand, ⌬26AUtE accumulated Ϸ5% of the wild-type ␤-subunit level, but approximately 60% of the wild-type RNA level. One possibility is that the 3Ј-UTR itself may affect translation; we have shown a correlation between atpB 3Ј processing and translation (25). However, the RT-PCR used here does not prove that the target transcript is intact and translatable.…”
Section: Influence Of 3 -Utr Tail Composition On Rna Accumulation In mentioning
confidence: 60%
See 3 more Smart Citations
“…On the other hand, ⌬26AUtE accumulated Ϸ5% of the wild-type ␤-subunit level, but approximately 60% of the wild-type RNA level. One possibility is that the 3Ј-UTR itself may affect translation; we have shown a correlation between atpB 3Ј processing and translation (25). However, the RT-PCR used here does not prove that the target transcript is intact and translatable.…”
Section: Influence Of 3 -Utr Tail Composition On Rna Accumulation In mentioning
confidence: 60%
“…These modified trnE genes were inserted as BglII-BamHI fragments into the BglII sites of atpB⌬19AD, atpB⌬21AD, and atpB⌬26AD [ Fig. 1 A and B; only the (A) 25 cassette was inserted into atpB⌬19AD and atpB⌬21AD]. For GFP constructs, plasmid MR220 containing cpgfp1 (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification of interactions between the two termini of cytoplasmic transcripts (18,19) and examples of 3Ј-UTR modulation of translation initiation in both eukaryotes (18,20) and prokaryotes (21)(22)(23) raise the possibility that interactions of the 5Ј-and 3Ј-UTR of chloroplast mRNAs may influence their expression. In support of this notion, recent results have shown that correct processing of the 3Ј-UTR can promote translation initiation and polysomal association (24).…”
mentioning
confidence: 51%